Simulation of single phase AC induction motor (capacitor start) by using MATLAB Simulink / Amir Hanifa Hussin - Hussin, Amir Hanifa (2010)
This thesis presents a simulation of single phase ac induction motor by using Matlab Simulink. This thesis report initially will discuss the basic operation of an AC single phase induction motor and the capacitor start single phase AC induction motor. Besides that, this thesis report also will discuss about the characteristic of single phase induction motor for the capacitor start type including the torque, speed and current including the characteristic of torque and starting current at the starting of motor operation. Matlab Simulink software is used in modelling and simulating the capacitor start of single phase ac induction motor.